Pengaruh Kondisi Sosial Ekonomi Terhadap Partisipasi Masyarakat Dalam Tertib Administrasi Kependudukan (Studi Kasus Dua Kelurahan Di Kota Denpasar) - Ernovianthy, A.A.Sg Erry; Murjana Yasa, I Gusti Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 1, Januari 2014 (pp. 1 - 47), 2014)
Stable economic conditions as well as the social and cultural conditions which better represents the main goal of development to achieve the welfare of the community. Is the active participation and involvement of the community in the implementation of government programs that have been planned. Low participation of the community development program resulted in the failure to meet it.This study aims to determine how high the level of community participation in the orderly administration of residence and how the influence of socio-economic conditions of people's participation in the orderly administration of residence.. Sub-district and village Padangsambian Sesetan are two villages that became the location of this study because it has the highest number of migrants from other villages in the city of Denpasar. Data were collected through structured interviews and non-participant observation with a sample of 120 respondents. Analitiqal techniques used are binary logistic. These result indicate the participation of village communities Padangsambian and Sesetan the orderly administration of relatively high population. Variables age, residence status, education level, household income, residence status and home ownership status simultaneously affect the people’s participation in orderly administration of population. Partially, the only variable between the variable home ownership status had no effect in orderly administration of population.
Keywords: community participation; population administration discipline; residence status; socio-economic conditions.